The Effect of Financial Literacy, Personality, and Financial Attitude on Financial Behavior Management in Malang SMEs - Melliya Yuliana; Dewi Nurjannah; Chalimatuz Sa’diyah (Universitas Muhammadiyah Malang, 2023)
The purpose of this research is to analyze financial literacy, personality, and financial attitude toward financial management behavior. The analytical tool used in this research is multiple linear regression analysis using SPSS 25. The population of this study is the owners of the SMEs in the trading sector in Karangploso District in 2022. Determination of the sample in this study used purposive sampling so that a total sample of 113 SMEs was obtained. The results of this study indicate that financial literacy, personality, and financial attitudes simultaneously influence the dependent variable. Partially, financial literacy, personality, and financial attitudes have a positive and significant effect on financial management behavior.